A Case of Severe Fioricet Withdrawal Presenting During Admission to an Inpatient Psychiatric Unit. (8th November 2021) - Rodulfo, Alejandro; Augsten, Alberto; Wainwright, Erin; Abramovici, Gil
Abstract : Background . Butalbital-containing combination (BCC) analgesics have the potential for the development of tolerance and dependence. Misuse and withdrawal of these agents should be considered in patients presenting with new-onset psychosis. This case highlights how butalbital withdrawal may be missed in the emergency department setting and underscores how early identification may affect management and prognosis. Case Presentation . A 40-year-old female with a history of migraine, depression, and anxiety presented to the emergency department (ED) with new-onset psychosis following a recent seizure-like episode. At home, the patient was prescribed butalbital-acetaminophen-caffeine (Fioricet), duloxetine, alprazolam, and zolpidem for these conditions. On arrival to the ED, the patient was disoriented and appeared to be responding to internal stimuli. Following initial medical evaluation, the patient was cleared for further psychiatric assessment, during which she developed acute-onset autonomic instability while waiting for a bed on the inpatient psychiatric unit. She then became agitated, requiring multiple emergency medications, and eventually required emergent intubation and was admitted to the intensive care unit (ICU). Following extubation, a psychiatric consultation was performed. On assessment, the patient was alert and oriented and no longer exhibited psychotic symptoms. She admitted to using butalbital-acetaminophen-caffeine (Fioricet) daily for the past 10 years and had recently run out of her prescribed medication. She acknowledged that she was taking more than prescribed and requested substance use treatment resources, for which she was subsequently discharged to an inpatient drug rehabilitation facility. Conclusions . Given the time constraints inherent to the ED setting, a complete substance use history (both illicit and prescribed) may be challenging to obtain. However, it remains critical for providers to identify patients at risk for life-threatening withdrawal from sedative, hypnotics, and anxiolytic agents.